PENGEMBANGAN GAME EDUKASI LABIRIN PADA ELEMEN KOMPUTER GRAFIS KELAS X DKV SMK NEGERI 1 GUNUNG TALANG - Firman Saputra; Haris Kurniawan; Herisvan Hendra (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Vocational education requires innovative learning media to adapt to technological developments and industrial needs. However, the condition at SMK Negeri 1 Gunung Talang shows that the use of learning media is still limited, causing students to be less motivated, especially in computer graphics subjects. This situation has an impact on low learning outcomes, where most students have not yet achieved the Minimum Mastery Criteria (KKTP). Therefore, the purpose of this study is to develop an educational maze game on computer graphics elements that is valid and practical, so it can help improve students’ understanding and learning motivation. The research method employed was Research and Development (RD) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were Grade X DKV students at SMK Negeri 1 Gunung Talang. Research instruments included media expert validation, material expert validation, as well as practicality tests by teachers and students. Data were collected through questionnaires, observations, and interviews. The development process involved designing the storyline and storyboard, creating the game using Construct 2 and CorelDraw, followed by implementation in the learning process, and evaluation based on validation and practicality results. The research results show that the developed maze educational game met the criteria of being highly valid, with an average media validity score of 88.46% and material validity of 95.83%. The practicality test indicated that the game was highly practical, with an average score of 97.22% from teachers and 89.48% from students. Thus, the maze educational game on computer graphics elements is considered feasible as a learning medium, as it effectively increases students’ interest, motivation, and understanding of the subject matter.